Great expectations? Female expatriates' perceptions of organisational performance and development reviews in supporting access to international assignments. Issue 2 (23rd April 2019) - Shortland, Susan; Perkins, Stephen J.
Abstract : Purpose: The purpose of this paper is to examine the role of organisational performance and development review policy and practice on women's access to international careers via long-term expatriate assignments in the oil and gas industry, with a specific focus on women's perceptions of procedural justice. Design/methodology/approach: A qualitative cross-sectional case study research design is used to analyse performance and development review, and international assignment policies in two firms, together with in-depth, semi-structured interviews with 14 Human Resource policy custodians and 21 female long-term current assignees. Findings: Women assignees do not see performance and development reviews as effective mechanisms to access expatriate roles. Nonetheless, women use these procedures while also operating within senior male networks to signal their desire to expatriate. Research limitations/implications: This study identifies differences between organisational policy objectives and policy implementation, and female assignees' experiences and expectations of accessing expatriate roles. Women's perceptions of organisational justice are not harmed because women place more emphasis on process and conversations than on policy. Research propositions are suggested extending organisational justice theory. Practical implications: Clear articulation of performance and development review processes aids organisational succession planning. Formalised, transparent expatriate career management supports women's access to expatriation. The roles of key personnel in determining access to expatriate career paths require clarification. Originality/value: This paper extends our knowledge of women's organisationally assigned expatriate careers and perceptions of procedural justice. Women use performance and development reviews to access expatriate opportunities. Employer action aligned to policy intent could help increase female expatriate participation.